Cancer cell-derived extracellular vesicles: a potential target for overcoming tumor immunotherapy resistance and immune evasion strategies - Ahn, Minseo; Mun, Jeong-Geon; Han, Yohan; Seo, Jae Ho (Frontiers in Immunology, 2025)
Extracellular vesicles (EVs), including exosomes and microvesicles, play crucial roles in cancer progression by mediating the communication between cancer cells and their microenvironment. Cancer cell-derived EVs promote tumor growth, metastasis, and immune evasion by carrying bioactive materials, such as proteins, RNAs, DNA fragments, and lipids but, immunotherapy aims to enhance the immune response against cancer; however, resistance remains a major challenge. Cancer cell-derived EVs contribute to this resistance by delivering immunosuppressive molecules that impair T cell activation, promote the expansion of regulatory T cells (Tregs), and reduce natural killer (NK) cell cytotoxicity, thereby allowing cancer cells to evade immune surveillance. Additionally, cancer cell-derived EVs can carry immune checkpoint proteins, such as Programmed Death-Ligand 1 (PD-L1), which bind to the Programmed Death-1 (PD-1) receptor on T cells, leading to T cell exhaustion and reduced anti-tumor activity. This mechanism reflects how cancer cells directly evade immune detection and contributes to the overall resistance to immune checkpoint blockade therapies, such as anti-PD-1 or anti-PD-L1 antibodies. By delivering these immunomodulatory molecules, EVs not only contribute to local immune suppression but also create a systemic environment that is less favorable for effective anticancer immunity. Therefore, understanding the role of EVs in the immunotherapy resistance is crucial for developing targeted strategies to counteract their effects and ultimately improve therapeutic outcomes. Here we encourage researchers to pay more attention to the role of cancer cell-derived EVs in overcoming immunotherapeutic resistance, because such efforts may be one of the most promising approaches to address immunotherapy resistance in the future.